2011
DOI: 10.1097/gme.0b013e31821b8484
|View full text |Cite
|
Sign up to set email alerts
|

Increased incident hip fractures in postmenopausal women with moderate to severe pelvic organ prolapse

Abstract: Objective To examine the association between fracture and pelvic organ prolapse (POP) in postmenopausal women enrolled in the Women’s Health Initiative Estrogen plus Progestin (WHI-EP) trial. Methods POP was assessed as cystocele, rectocele or uterine prolapse, and was graded as “absent-to- mild” or “moderate-to-severe”. Cox proportional hazard analyses (adjusting for age, BMI, race, asthma, emphysema, thyroid disease, family history of fracture, regular menses, age at menopause, nulliparity, history of horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…This inhibition may be caused by genetic factors that are associated with the original collagen metabolism, cell cycle or apoptosis, which result in POP. Furthermore, Pal et al concluded that moderate to severe POP is an independent predictor of incident spine [hazard ratio (HR), 2.61; 95% confidence interval (CI), 1.04–6.56; P=0.042] and lower arm fractures (HR, 1.87; 95% CI, 1.06–3.29; P=0.030) ( 23 ). Feola et al demonstrated that worsening pelvic supportive ability was negatively correlated with decreased collagen alignment (r 2 =−0.66) and mechanical properties (r 2 =−0.67) ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition may be caused by genetic factors that are associated with the original collagen metabolism, cell cycle or apoptosis, which result in POP. Furthermore, Pal et al concluded that moderate to severe POP is an independent predictor of incident spine [hazard ratio (HR), 2.61; 95% confidence interval (CI), 1.04–6.56; P=0.042] and lower arm fractures (HR, 1.87; 95% CI, 1.06–3.29; P=0.030) ( 23 ). Feola et al demonstrated that worsening pelvic supportive ability was negatively correlated with decreased collagen alignment (r 2 =−0.66) and mechanical properties (r 2 =−0.67) ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although a correlation between muscle strength and bone mineral density has been observed in women with early menopause [ 13 ], there is conflicting evidence on the relationship between decreased muscle strength indicated by isometric and isokinetic tests and decreasing levels of bone mineral density [ 14 , 15 , 16 ]. In this line, some studies have reported little or no association between these factors [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1,1014] A correlation has been shown between skeletal fragility and POP in postmenopausal women. [15,16]…”
Section: Introductionmentioning
confidence: 99%